A Process-Tracing Study of Brand Extension Evaluation - Boush, David M.; Loken, Barbara (Journal of marketing research, 1991)
The authors explore the implications of considering a brand as representing a category consisting of its products. They report results of a laboratory experiment in which response times and verbal protocols were used to examine processes related to the evaluation of brand extensions. Evaluations of brand extensions were influenced both by the extension's similarity to the brand's current products (brand extension typicality) and by the variation among a brand's current products (brand breadth). An inverted U describes the relationship between brand extension typicality and evaluation process measures. Moderately typical extensions were evaluated in a more piecemeal and less global way than were either extremely typical or extremely atypical extensions. Subjects' attitudes toward brand extensions were correlated highly with their ratings of brand extension typicality.